Prevalence of selected infectious disease agents in stray cats in Catalonia, Spain - Ravicini, Sara (JFMS Open Rep, 2016)
OBJECTIVES: The objective of the current study was to investigate the prevalence rates of the following infectious agents in 116 stray cats in the Barcelona area of Spain: Anaplasma phagocytophilum, Bartonella species, Borrelia burgdorferi, Chlamydia felis, Dirofilaria immitis, Ehrlichia species, feline calicivirus (FCV), feline herpesvirus-1 (FHV-1), feline leukaemia virus (FeLV), feline immunodeficiency virus (FIV), haemoplasmas, Mycoplasma species and Rickettsia species. METHODS: Serum antibodies were used to estimate the prevalence of exposure to A phagocytophilum, Bartonella species, B burgdorferi, Ehrlichia species and FIV; serum antigens were used to assess for infection by D immitis and FeLV; and molecular assays were used to amplify nucleic acids of Anaplasma species, Bartonella species, C felis, D immitis, Ehrlichia species, FCV, FHV-1, haemoplasmas, Mycoplasma species and Rickettsia species from blood and nasal or oral swabs. RESULTS: Of the 116 cats, 63 (54.3%) had evidence of infection by Bartonella species, FeLV, FIV or a haemoplasma. Anaplasma species, Ehrlichia species or Rickettsia species DNA was not amplified from these cats. A total of 18/116 cats (15.5%) were positive for FCV RNA (six cats), Mycoplasma species DNA (six cats), FHV-1 DNA (three cats) or C felis DNA (three cats). CONCLUSIONS AND RELEVANCE: This study documents that shelter cats in Catalonia are exposed to many infectious agents with clinical and zoonotic significance, and that flea control is indicated for cats in the region.